Dances with wolves - Wilson, Jim; Costner, Kevin; Metro-Goldwyn-Mayer; Orion Pictures release; Tig Productions ([Burbank, CA] : Tig Productions, 1990)
A historical drama about the relationship between a Civil War soldier and a band of Sioux Indians. Attracted by the natural simplicity of their lifestyle, John W. Dunbar chooses to leave his former life behind to join them, taking on the name Dances with Wolves. Soon, Dances with Wolves has become a welcome member of the tribe and fallen in love with a white woman who has been raised amongst the tribe. His peaceful existence is threatened, however, when Union soldiers arrive with designs on the Sioux land
Title from title screen
Originally produced as a motion picture in 1990
Director of photography, Dean Semler ; edited by Neil Travis ; music composed and conducted by John Barry
Cast: Kevin Costner, Mary McDonnell, Graham Greene, Rodney A. Grant
DVD format
With English subtitle
Keywords: Dakota Indians -- South Dakota -- Drama; Indians of North America -- Great Plains -- Drama